Perbandingan Anestesi Xylazin-Ketamin Hidroklorida dengan Anestesi Tiletamin- Zolazepam terhadap Frekuensi Denyut Jantung dan Pulsus Anjing Lokal - Darmayudha, Anak Agung Gde Oka; Gorda, I Wayan (Buletin Veteriner Udayana, 2012)
A study to determine the effect of anesthesia xylazine- ketamine hydrochlorida withanesthesia tiletamine-zolazepam administration to heart pulse frequency and pulse duringanesthetion. The experimental was carried duct on local dog. The experimental design usewas a splite in time with 2 treatment : treatment I xylazin-ketamin ( 2 mg/Kg Body weightof xylazine ; 15 ing/Kg Body weight ketarnine) and treatment II tiletamine-zolazepam ( 20mg/Kg Body weight). Each treatment use 5 dogs as refrain so we use 10 dogs for all of thetreatment. Obtain data is analized by various investigated test. Result of this study indicatedthat difference of treatment there were no significance, but time of the observed duringanesthesion showed more highly significance and significant to pulse frequency.
Keywords: xylazine-ketamine, tiletamine-zolazepam, heart pulse frequency, pulse frequency, local dogs